Assessment of Forward Osmosis in PRO Mode during Desalination of a Local Oil Refinery Effluent - Elorm Obotey Ezugbe (MDPI AG, 2021)
In this study, the performance of a forward osmosis system was assessed over a 30-h period during desalination of a local oil refinery effluent using NaCl as the draw solute. The study was conducted with the active layer of the membrane facing the draw solution. Assessment was done based on the water flux, salt rejection (SO42− and CO32−), membrane fouling and fouling reversal after membrane cleaning. Critical to this study was the performance of manual scrubbing of the membrane after each run and the application of chemically enhanced osmotic backwash. Scanning electron microscope (SEM) analysis of the cellulose triacetate (CTA) membrane was conducted before and after cleaning to ascertain the degree of fouling and fouling reversal after membrane cleaning. The results showed an average water flux of 3.78 ± 0.13 L/m2 h, reverse solute flux (RSF) of 1.56 ± 0.11 g/m2·h, SO42− rejection of 100%, CO32− rejection of 95.66 ± 0.32% and flux recovery of 95% after membrane cleaning. This study identifies that intermittent manual scrubbing of the membrane plays a major role in overall membrane performance. It also provides a practical basis for further research and decision making in the use of FO and CTA membranes for oil refinery effluent desalination.